Promoting psychological adaptation among navy sailors - Van Wijk, Charles H; Martin, Jarred H (Scientia Militaria - South African Journal of Military Studies, 2021)
The mandate of the Institute for Maritime Medicine (IMM) is to support and enhance the operational performance of sailors of the South African Navy during maritime operations, while also ensuring positive long-term mental health outcomes of sailors who serve their country at sea. To achieve this, the IMM proposes to re-orientate the mobilisation and demobilisation programmes used for ship-based maritime operations towards a predict-and-promote (P&P) approach, to enhance the psychological adaptation of sailors to the emotional demands of deployment as well as to support more adaptive forms of mental health resilience, both before and after sea-going operations. First, this article aims to present the proposed P&P approach for enhancing psychological adaptation during and after seaward deployments, with a specific focus on assessing personal emotional regulation (ER). For effective implementation, this approach is contingent on several clinical assumptions about ER in the operational environment, namely: the absence of significant psychopathology; the stability of the ER measure; the role of dispositional factors in operational adaptation; and the availability of population-specific normative data, which act as an interpretative guide of ER profiles for sailors. The second aim is to consider support for these assumptions, using previous experience during the mobilisation and/or demobilisation of ships involved in maritime operations. Support was found for all four assumptions, indicating the clinical and operational utility of the P&P approach at the IMM broadly, and the assessment of ER for sailors in particular.